The Development System of Linguistic Experience on The Debate Text of Presidential Candidate of The Republic of Indonesia 2014 – 2019 - Setiawan, Irma; Setiawan, Irma; Darma Laksana, I Ketut; Mahyuni, Mahyuni; Udayana, I Nyoman (e-Journal of Linguistics; Vol 13 No 2 (2019): e-jl-July, 2019)
The presidential candidate debate text development system is a sort of linguistic experience elements reflecting the speaker's way of thinking related to the policies of the nation and state. The text development might indicate the policy intended by a presidential candidate to build the nation and state. Based upon this, there are three factors behind the selection of this topic to research; namely, empirical, practical, and theoretical factors. This study is conducted aimed at describing various issues concerning the development of the linguistic experience of the two presidential candidates in improving the national and international welfare and international politics-national resilience. Systemic Functional Linguistic (SFL) theory initiated by Halliday (1985,1991, 2004, 2014) is used as the grounded theory in this study. This study employs qualitative descriptive approach with linguistic phenomenological paradigm. Various data types analyzed in this study include words, phrases, clauses, group phrases, and text units. The data use taken from the recorded of audio-visual Candidate Debate Text (CDT) in stage I and II. The research instruments used in this study are text validation tables and contexts. Along with some advanced techniques, documentation and observation were conducted to collect the data. Meanwhile, in processing the data collected, this study passed several stages; namely, data classification, segmentation, and codification. To analyze the data processed, this study employed several stages namely reduction, presentation, and verification. The results of this study show that Prabowo Subianto (PS) tended to use dynamic linear text development pattern, whereas Joko Widodo (JW) tended to use a constant linear text development pattern.